Perancangan Sarana Bawa Multifungsi dengan Konsep Knockdown untuk Fasilitas Fun Football dan Bekerja Kantoran - Ryu Kafa Basuni; Mohamad Arif Waskito (Penerbit Itenas, 2025)
This design aims to produce a multifunctional backpack-type carrying facility as a practical and safe facility for carrying office work and football equipments, intended for men aged 20-29 years, working as office workers and whose hobby is football. This research is based on the need for carrying facilities that can assist mobility and be safe when carrying both types of luggage, namely football sports equipment and work equipment, thereby creating the potential for damage due to the mixing of these two types of luggage. To achieve the research objectives, a knockdown design concept was used with several compartments that can be removed and installed as needed. This allows users to adapt tasks to the activities they perform. The bags are designed taking into account the characteristics of urban society and the visual character of sports. Its compact size and light weight make it easy to carry anywhere. The method or approach used in this design is a double diamond which consists of four stages, namely Discover, Define, Develop, Deliver. The design begins with the Discover stage through distributing questionnaires, observing community activities, interviews, and being directly involved with several activities in the community. This design ends with the Deliver stage through the 3D modeling stage with sizes and functions that have been adjusted to the resulting design.